Observation and modeling research of high-velocity flushing effect on the performance of BEAM. Issue 1 (September 2016) - Zhang, Fawang; Gu, Lin; Chen, Jipeng; Xu, Hui; Zhao, Wansheng
Abstract Blasting erosion arc machining (BEAM) is a novel high efficiency electrical erosion process, which is characterized by a powerful multi-hole inner flushing. In order to study the influence of the high-velocity flushing on the performance of BEAM, a single discharge experiment is carried out on a specially designed observation apparatus, and the phenomena that occurred during the discharge is observed using a high-speed video camera. During the discharge process, a spray cloud of the removed debris near the downstream side of the discharging point is captured by the camera. Tail shaped crater and erosion-corrosion features are also found on the workpiece and electrode surfaces, respectively. These observed phenomena imply that the high-velocity flushing can greatly improve the melting metal removal from the molten pool thereby improving the material removal rate (MRR). For purpose of exploring the mechanism behind, the flow field and pressure distribution of the high-velocity flushing are analyzed by using computational fluid dynamic (CFD) method. The analyzed results indicate that a low-pressure suction effect exists on the downstream side of the electrodes. With the help of the low-pressure suction effect, the high-velocity flushing can continuously take the molten metal out of the molten pool during the discharge, resulting in the reduction of the overheating of the molten metal and improve the efficiency of the discharging energy. Thereby, the work in this paper helps to explain why the high-velocity flushing can markedly promote the material removal rate.